ARAH POLITIK PENDIDIKAN ISLAM INDONESIA ABAD KE 21 - Rahmatullah, M. Asep; Munawati, Siti; Suryagalih, Sugih (Universitas Islam Syekh Yusuf, 2019)
Abstarct The Political Direction of Islamic Education In the 21st century, history has noted that Islamic education in Indonesia has taken root since the entry of Islam into the archipelago, that Islamic education is perfectly upright and perfect is inseparable from the role of the sultans, scholars, and Muslims continues to try to carry out the study of science majors , discussion, writing in the context of jihad fi sabillilah tafaqohu fiddien for the glory of Islam. It is also supported by Islamic political policies that are very beneficial for the interests of the world of Islamic education. Since the destruction of the Caliphate of the Ottoman Turkish Islamic government and the destruction of the Islamic kingdoms in Indonesia and the world. Then the condition of Islamic education experienced ups and downs and the lack of support from the Indonesian government. Therefore, after Indonesia's independence and the increasingly open world of globalization and modernization, it is necessary to look for ideas and ideal forms that are integrally holistic for the world of Islamic education. As well as being able to influence the policies of the Indonesian government and master the political policies of 21st century Islamic education for the future of Indonesian Muslims.Abstark Arah Politik Pendidikan Islam Abad ke 21, sejarah telah mencatat bahwa pendidikan Islam di Indonesia telah mengakar dari sejak masuknya Islam ke nusantara, pendidikan Islam tegak secara sempurna dan paripurna tidak lepas dari peranan para sultan, ulama, dan kaum muslimin yang terus berupaya melakukan kajian majlis ilmu, diskusi, menulis serta aktif dalam gerakan dakwah dan jihad fi sabillilah untuk kejayaan islam. Setelah menancapkan kekuasaan Islam, maka sistem pendidikan islam di topang oleh kebijakan politik Islam yang sangat menguntungkan bagi kepentingan dunia pendidikan Islam. Sejak kehancuran kekhalifahan pemerintahan Islam turki utsmani dan kehancuran kerajan-kerajaan Islam di Indonesia dan dunia. Maka kondisi pendidikan Islam mengalami pasang surut kemunduran dan kurangnya dukungan pemerintah Indonesia. Oleh karena itu, setelah Indonesia merdeka dan semakin terbukanya dunia globalisasi dan modernisasi, maka perlu mencari ide, dan format yang ideal secara integralistik holistik untuk dunia pendidikan Islam. Serta dapat mempengaruhi kebijakan pemerintah Indonesia dan menguasai kebijakan politik pendidikan Islam abad ke 21 untuk masa depan umat Islam bangsa Indonesia.